PENGARUH KEPEMIMPINAN,MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN HOTEL HORISON SEMARANG (Studi Pada Hotel Horison Semarang) - Cholida Zulkarima, 14.05.51.0114; Suhana, Suhana (Students' Journal of Economic and Management, 2018)
This study aims to test and analyze the influence of leadership , motivation , and workplace environment against employee performance in Hotel Horizon Semarang. Respondents this research consist of 97 employees. Model of the data analysis that is used is product moment, with reliability test cronbach alpha and linear regression analysis spss 20,0 version to examine and prove a research hypothesis .The data collected following the completion of testing the results all data expressed valid and reliable .The result of research that: ( 1 ) leadership has a positive and significant effects on employee performance , ( 2 ) motivation has a positive and significant effects on employee performance , and ( 3 ) work environment has a positive e and significant effects on employee performance . Based on the test conducted all data valid and reliable. Keyword : Leadership, Motivation, Work environment, Employees performance